2014
DOI: 10.1139/cjm-2013-0864
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and analysis of a novel metalloprotease gene of entomopathogenic Serratia marcescens strains in infected Galleria mellonella

Abstract: Serratia marcescens strains isolated from entomopathogenic nematodes (Rhabditis sp.) were examined for their pathogenicity and establishment in wax moth (Galleria mellonella) larvae. All the Serratia strains were potently pathogenic to G. mellonella larvae, leading to death within 48 h. The strains were shown to possess a metalloprotease gene encoding for a novel serralysin-like protein. Rapid establishment of the bacteria in infected larvae was confirmed by specific polymerase chain reaction (PCR) detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
(40 reference statements)
1
4
0
1
Order By: Relevance
“…The extract of S. marcescens marcescens IBUN-090-00706 presented insecticide activity by ingestion. This result is in concordance with the study of Tambong et al (2014), in which the authors reported insecticidal activity against Galleria mellonella. However, the methodology was different as they injected active bacterial cells directly into the insect hemocele (most studies on entomopathogenic bacteria are done this way), contrary to this study, in which the insecticidal capacity of extracts without active bacterial cells was evaluated; in the case of this bioassay, extracts were demonstrated to act by ingestion against leaf-cutting ants.…”
Section: Discussionsupporting
confidence: 93%
“…The extract of S. marcescens marcescens IBUN-090-00706 presented insecticide activity by ingestion. This result is in concordance with the study of Tambong et al (2014), in which the authors reported insecticidal activity against Galleria mellonella. However, the methodology was different as they injected active bacterial cells directly into the insect hemocele (most studies on entomopathogenic bacteria are done this way), contrary to this study, in which the insecticidal capacity of extracts without active bacterial cells was evaluated; in the case of this bioassay, extracts were demonstrated to act by ingestion against leaf-cutting ants.…”
Section: Discussionsupporting
confidence: 93%
“…The S. litura larvae infected with S. marcescens and E. mundtii showed the symptoms of lethargy, dark colouration of body, flaccid with intact integument which are typical symptoms of bacterial infection 40 . Likewise P. interpunctella and E. kuehniella infected with S. marcescens showed similar symptoms of infection 32 , 34 , 36 , 41 .…”
Section: Discussionmentioning
confidence: 72%
“…Serratia spp., is a gram-negative bacterium (Enterobacteriaceae) containing insect pathogenic strains (Tambong et al, 2014) against several insect species including locusts (Tao et al, 2006(Tao et al, , 2007. There are more than 70 spesies of insects are susceptible to Serratia infections including insects from order orthoptera, isopteran, coleoptera, lepidoptera, hymenoptera and diptera (Grimont et al, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…However, further studies are needed to confirm the effects of this bacterium to human health and other important organisms. Metalloproteases produced by S. marcescens are potential to be developed for biological control of important insect pests (Tambong et al, 2014)…”
Section: Resultsmentioning
confidence: 99%